A520 MOF-derived alumina as unique support for hydrogen production from methanol steam reforming: The critical role of support on performance. (August 2020) - Khani, Yasin; Kamyar, Niloofar; Bahadoran, Farzad; Safari, Nasser; Amini, Mostafa M.
Abstract: In the present study, the role of support as a crucial parameter on the performance of the methanol reforming catalysts was investigated. In this work, commercial A520 MOF derived γ-Al2 O3 [Al2 O3 (A)] was applied as a support for Cu and Pd active. Other catalysts over γ-Al2 O3 (Merck) [Al2 O3 (M)] and A520 MOF were also prepared. The fabricated catalysts were identified by techniques such as XRD, BET surface area, EDS mapping, FESEM, and H2 -TPR. The performance of catalysts in methanol steam reforming (MSR) process was evaluated in the temperature range of 150–300 °C. The highest methanol conversion (97%) and H2 yield (98%) were attained for Pd/Al2 O3 (A) among all catalysts. Also, the highest (7.3%) and lowest (2.6%) CO selectivity were obtained for catalysts Cu/Al2 O3 (M) and Pd/Al2 O3 (A), respectively. The TGA disclosed almost no coke formation for Pd/Al2 O3 (A) catalyst after 30 h on stream. Graphical abstract: Methanol steam reforming reaction was investigated using copper and palladium metals supported on A520 MOF, MOF-derived alumina, and commercial alumina. Image 1 Highlights: Cu and Pd performance over A520 MOF-derived alumina were studied in the MSR process. Formation of coke on the Pd/Al2 O3 catalyst in the MSR process was insignificant. Conversion of methanol was influenced by A520 MOF-derived alumina support.